ANALISIS GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN - Paisal, Paisal (Jurnal Manajemen, 2019)
This study aims to analyze the extent to which leadership styles affect the performance and leadership style which dominant influence on performance. This research uses leadership style as independent variable and performance as dependent variable. The sample used is all employees of PT Nindya Karya (Persero) Palembang as much as 71 respondents. The analytical technique used consists of qualitative and quantitative methods by using SPSS data processing application program version 19 for windows. The result of this research show that leadership style have influence to performance equal to 10,492, and dominant leadership style variables influencing to performance exist in supportive style of leadership equal to 3,705, The writer conclude that company should still maintain suportive leadership style to improve employee performance.